Inhibiting Glycine Decarboxylase Suppresses Pyruvate-to-Lactate Metabolism in Lung Cancer Cells - Woo, Chern Chiuh; Kaur, Kavita; Chan, Wei Xin; Teo, Xing Qi; Lee, Teck Hock Philip (Frontiers in Oncology, 2018)
Glycine decarboxylase (GLDC) gene is frequently upregulated in various types of cancer including lung, prostate and brain. It catabolizes glycine to yield 5,10-methylenetetrahydrofolate, an important substrate in one-carbon metabolism for nucleotide synthesis. In this study we used exon splicing modulating steric hindrance antisense oligonucleotide (shAON) to suppress GLDC expression and investigated its effect on pyruvate metabolism via hyperpolarized carbon-13 magnetic resonance spectroscopy (MRS). The MRS technique allows us to study in vivo metabolic flux in tumor tissues with/without GLDC-shAON intervention. Here we show that GLDC-shAON treatment is able to suppress lung cancer cell growth and tumorigenesis, both in vitro and in vivo. The carbon-13 MRS results indicated that the conversion of pyruvate into lactate in GLDC-shAON treated tumor tissues was significantly reduced, when compared to the control groups. This observation corroborated with the reduced activity of lactate dehydrogenase and pyruvate dehydrogenase in GLDC-shAON treated lung cancer cells and tumor tissues. Glycolysis stress test showed that extracellular acidification rate was significantly suppressed after GLDC-shAON treatment. Besides lung cancer, the antitumor effect of GLDC-shAON was also observed in brain, liver, cervical and prostate cancer cell lines. Furthermore, it enhanced the treatment efficacy of cisplatin in lung cancer cells. Taken together, our findings illustrate that pyruvate metabolism decreases upon GLDC inhibition, thereby starving cancer cells from critical metabolic fuels.